The quest for environmental sustainability in educational institutions - Kumar, Nand; Kumar, Ashwani; Sharma, Sunil (International Journal of Engineering and Technology, 2018)
Over the last four decades â€œSustainable Developmentâ€ has emerged as a catchphrase while defining development. Many reforms have taken up in the past to solve ever-increasing snags related to untenable development at local as well as global level. However, the review of literature pertaining to sustainable development shows that it lacks in proper interpretation and consistency in the definition across the globe. Further, itâ€™s the environmental sustainability aspect that has been compromised again and again to give way to economic development. In practice, environmental sustainability is not considered as equally significant in comparison to the other two aspects of sustainability. The issues of sustainability in educational institutions have historical pedigree starting from Stockholm Declaration, Tbilisi Declarations and subsequently a lot of evolution has taken place in this field. Still, most of the educational institutions lack their roadmap to attain sustainable development. Some of the universities have tried to implement their own sustainability plan apart from signing any major declaration. This review paper suggests that environmental sustainability is the need of the hour and this concept need more workable, elaborated and practical solution which need to be free from political bias and possess intellectual clarity and objectivity.